Baltimore revisited : stories of inequality and resistance in a U.S. city - King, P. Nicole, 1976-; Drabinski, Kate S.; Davis, Joshua Clark (New Brunswick : Rutgers University Press, 2019)
"Nicknamed both "Mobtown" and "Charm City" and located on the border of the North and South, Baltimore is a city of contradictions. From media depictions in The Wire to the real-life trial of police officers for the murder of Freddie Gray, Baltimore has become a quintessential example of a struggling American city. Yet the truth about Baltimore is far more complicated--and more fascinating. To help untangle these apparent paradoxes, the editors of Baltimore Revisited have assembled a collection of over thirty experts from inside and outside academia. Together, they reveal that Baltimore has been ground zero for a slew of neoliberal policies, a place where inequality has increased as corporate interests have eagerly privatized public goods and services to maximize profits. But they also uncover how community members resist and reveal a long tradition of Baltimoreans who have fought for social justice. The essays in this collection take readers on a tour through the city's diverse neighborhoods, from the Lumbee Indian community in East Baltimore to the crusade for environmental justice in South Baltimore. Baltimore Revisited examines the city's past, reflects upon the city's present, and envisions the city's future"--
Frontmatter -- Contents -- Foreword / Shopes, Linda -- Introduction: Why Revisit Baltimore Now? / King, P. Nicole / Davis, Joshua Clark / Drabinski, Kate -- Part I. Place and Power: Roots of (In)Justice in the City -- 1. The City That Eats: Food and Power in Baltimore's Early Public Markets / Gamble, Robert J. -- 2. "Shove Those Black Clouds Away!": Jim Crow Schools and Jim Crow Neighborhoods in Baltimore before Brown / Lieb, Emily -- 3. "The Pot": Criminalizing Black Neighborhoods in Jim Crow Baltimore / Casiano, Michael -- 4. Vacant Houses and Inequality in Baltimore from the Nineteenth Century to Today / Pousson, Eli -- 5. A Psychology of Place: Race, Violence, and Community in Baltimore / Buccino, Daniel / Méndez, Teresa -- 6. Community Health and Baltimore Apartheid: Revisiting Development, Inequality, and Tax Policy / Brown, Lawrence -- Part II. Histories of Contestation and Activism in a Legacy City -- 7. The Riot Environment: Sanitation, Recreation, and Pacification in the Wake of Baltimore's 1968 Uprising / Fredrickson, Leif -- 8. "The People's Side of the Road": Movement against Destruction and Organizing across Lines of Race, Class, and Neighborhood / Darrow, Shannon -- 9. More Than a Store: Activist Businesses in Baltimore / Davis, Joshua Clark -- 10. "Welfare Isn't a Single Issue": Baltimore's Welfare Rights Movement, 1960s-1980s / Zanoni, Amy -- 11. The Last Censors: The Life and Slow Death of Maryland's Board of Motion Picture Censors, 1916-1981 / Tropea, Joe -- 12. "Temple of the Drama" The Five-Year Protest at Ford's Theater, 1947-1952 / Ferretti, Jennifer A. -- Part III. Voices from Here: Listening to the Past -- 13. "Because They Were Also Downed People": Black-Jewish Relationships in Baltimore during the 1968 Uprising and Beyond / Levin, Jacob R. -- 14. (snapshot) Korean Communities in Baltimore / Hyun-Jin Shin, Ale Theia -- 15. The Lumbee Community: Revisiting the Reservation of Baltimore's Fells Point / Minner, Ashley -- 16. Overburdened Bodies and Lands: Industrial Development and Environmental Injustice in South Baltimore / Fabricant, Nicole -- 17. Finding Closure: The Poets of the Sparrows Point Steel Mill / Stefano, Michelle L. -- 18. Baltimore's Socialist Feminists -- Lessons from Then, Lessons for Now: Community Empowerment and Urban Collectives in the 1970s / Kalogeropoulos, April / Morrow Nix, Elizabeth / Kelber-Kaye, Jodi -- 19. Relentlessly Gay: A Conversation on LGBTQ Stories in Baltimore / Drabinski, Kate / Parker Kelley, Louise -- Part IV. Surviving in the Neoliberal City: Redevelopment in Baltimore -- 20. Johns Hopkins University and the History of Developing East Baltimore / Gomez, Marisela B. -- 21. Image and Infrastructure: Making Baltimore a Tourist City / Rizzo, Mary -- 22. Skywalk: The Life and Death of Multilevel Urbanism in Downtown Baltimore / Scharmen, Fred -- 23. Rethinking Gentrification in Baltimore, Sharp Leadenhall / Durington, Matthew / Collins, Samuel Gerald -- 24. The Superblock: A Downtown Development Debacle, 2003-2015 / King, P. Nicole -- 25. Under Armour's Global Headquarters and the Redevelopment of South Baltimore / Otten, Richard E. -- Part V. Democratizing the Archives -- 26. Social History in the Archives: Baltimore's Enduring Legacy / Faust, Aiden -- 27. Building a More Inclusive History of Baltimore: Preserving the Baltimore Uprising / Meringolo, Denise D. -- Afterword: Weaving Knowledges / Stocks, Shawntay -- Acknowledgments -- Notes on Contributors -- Index
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Urban policy -- Maryland -- Baltimore; Sociology, Urban -- Maryland -- Baltimore; Income distribution -- Maryland -- Baltimore; Equality -- Maryland -- Baltimore; Baltimore (Md.) -- Social conditions; Politique urbaine -- Maryland -- Baltimore; Sociologie urbaine -- Maryland -- Baltimore; Revenu -- Répartition -- Maryland -- Baltimore; HISTORY -- United States -- State & Local -- Middle Atlantic (DC, DE, MD, NJ, NY, PA); POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; SOCIAL SCIENCE -- Discrimination & Race Relations; ARCHITECTURE -- Urban & Land Use Planning; SOCIAL SCIENCE -- Sociology -- Urban; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; SOCIAL SCIENCE -- Social Classes; Equality; Income distribution; Social conditions; Sociology, Urban; Urban policy; Maryland -- Baltimore